Nanometers and Gigabucks - Moore, Gordon E. (1996)
Filmed for the Leaders in Computer Science and Electrical Engineering Distinguished Lecture Series XII, this talk from Gordon E. Moore (1929-2023) covers the history and future of the semiconductor industry (as of 1996). Moore walks through the development of the earliest transistors, the creation and limitations of Moore's Law, and the economics of producing future technology.
Keywords: Semiconductors; Moore, Gordon E., 1929-; Intel Corporation; Integrated circuits; Computers--History